ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN KOPERASI SIMPAN PINJAM DUA MUARA KOTA MANNA TAHUN 2015-2017 - Febriansyah, Erwin; Yulinda, Ade Tiara; Purnamasari, Diah (JURNAL EKOMBIS REVIEW, 2019)
The formulation of the problem in this study is how financial performance of Dua Muara of saving loan cooperative in the city of manna in 2015-2017 seen from ratio liquidity, solvency and provability.The purpose of this study is to determine financial performance of  simpan pinjam cooperative  in the city of manna in 2015-2017 seen from ratio liquidity, solvency and provability.The object of this researchis the Financial report of Dua Muara of saving loan cooperative in the city of manna in 2015-2017.  Data analysis technique used in this reseach  are quantitative  descriptive and interpretating of the data so that it can give Clear description under study Using financial formulation. The result of analysis trough financial report of Dua Muara of saving loan cooperative using financial are report good enough. So it can be conclude that financial performance of of Dua Muara of saving loan cooperative are good enough  but it is necessary to improve the calculation of the financial statement